Formulation and Activity Test Of Oil Spray Deodorant Preparations In Black Cumin Seeds (Nigella Sativa L.) Against Staphylococcus Epidermidis Causes Of Body Odor - Alyidrus, Rugayyah; Ramadhani, Rezki; Santi, Elvira; Awaluddin, Nurhikma; Alydrus, Nur Laela (Sean Institute, 2024)
Staphylococcus epidermidis bacteria are able to convert amino acids into isovaleric acid which causes unpleasant odors. This research aims to determine whether the essential oil of black cumin seeds (Nigella sativa L.) can be formulated into a deodorant spray physically stable and it has activity against Staphylococcus epidermidis which causes body odor. The research method was laboratory experimental using water distillation to extract essential oils and formulate deodorant spray preparations with concentrations of F1 (1%), F2 (3%), and F3 (5%). Evaluation of preparations includes organoleptic tests, homogeneity tests, pH tests, viscosity tests, spray pattern tests, dry time tests, emulsion type tests, irritation and hedonic tests, stability tests and antibacterial activity tests of preparations. The results of the research showed that the evaluation of the deodorant spray preparation of essential oil of black cumin seeds (Nigella sativa L.) had a P value of >0.05 so that this preparation was physically stable, while the statistical results of the antibacterial activity test obtained a P value of <0.05 indicating that there was a significant difference. This preparation has different activity diameters, including F1 (1%) in the medium category at 8.47 mm, F2 (3%) and F3 (5%) in the strong category with activity above 10-20 mm. It was concluded that the essential oil of black cumin seeds (Nigella sativa L.) can be formulated into a deodorant spray that is physically stable and has activity against Staphylococcus epidermidis which causes body odor